ANALISIS NILAI TAMBAH BISNIS BUDIDAYA IKAN BANDENG (Chanos chanos) DI DESA LABULU-BULU KECAMATAN PARIGI KABUPATEN MUNA - Abdul Rahim; La Onu La Ola; Abdul Muis Balubi (UNIVERSITAS HALU OLEO, 2022)
This research was conducted in Labulu-Bulu Village, Parigi District, Muna Regency from November to December 2018, with the aim of this rescardi is to study the business process of milkfish farming in Labulu-Bulu Village and assessing the value added created by the milkfish farmiy business. The number of respondents in this study were 3 business people in milkfish farmiy business obtained through purposive sampling. Data obtained through direct interviews using a questionnaire. The research variables measured and observed are the production process, costs, production quantities and prices. The data obtained were analyzed using profit analysis with the formula π = TR-TC and the added value with the formula NT = G + Pt + Pj + π. The amount of milkfish fish production per cycle was 28,700 kg; fixed costs amount is was to Rp118,313,018,9; variable costs in the amount of Rp172,105,000, with an average total cost of Rp. 96,806,006.3; the amount of milkfish business revenue is Rp.430,500,000, with an average profit of Rp.46,693,993.7 and an average added value of Rp120,806,667. The highest profit gained by the milkfish business man was Rp. 198,000,000 and the lowest profit was Rp76,500,000, while the highest added value was Rp. 167,630,000 and the lowest value added was Rp. 62,280,000. The results of the profit analysis show that the total profit value is Rp140,081,981 and the added value shows an average added value of Rp362,420,000. Keywords: Milkfish Cultivation, Benefits, Value Added